Relationship between clinical contourometric measurements and vertebral rotation in adolescent idiopathic scoliosis - Čimić, Mislav (Array, 2009)
Summary: The relationship between trunk and spine deformity has yet not been well defined. The purpose of this study was to identify the relationship between clinical (contourometric) and radiographic methods of scoliotic deformity evaluation. Our second objective was to create mathematical formulas for calculating radiographic parameters based on defined correlations of multiple parameters. We did a study of 136 preoperatively analysed patients with idiopathic scoliosis. Altogether, 189 lateral curvatures were assessed. Based on Lenke’s classification, curves were divided into three groups: a thoracic, a thoracolumbar and a lumbar curve group. Each group was analyzed separately to determine relationships between clinical contourometric (scoliometer value, humpometer values) and radiographic measurement (apical vertebral rotation (AVR) according to Drerup). On the grounds of statistically significant correlation coefficients of most clinical parameters and Drerup rotation we found good relationships between trunk and spine deformity. Using the best correlated clinical parameters and multiple regression statistical analysis we created mathematical formulas for prediction of scoliotic AVR in higher degree curves